Airway foreign body manifested as a coin lesion. Issue 9 (8th August 2018) - Nishinaga, Yuko; Miyazaki, Shinichi; Yamashita, Ryo; Ikeda, Takuya
Key Clinical Message: Foreign body aspiration is a potentially life‐threatening event. The nature of the inhaled objects is highly variable, ranging from organic to inorganic material. Although most pills are radiolucent, lanthanum carbonate is radiopaque and may be identified on chest X‐rays. Abstract : Foreign body aspiration is a potentially life‐threatening event. The nature of the inhaled objects is highly variable, ranging from organic to inorganic material. Although most pills are radiolucent, lanthanum carbonate is raradiopaque and may be identified on chest X‐rays.